KEMAMPUAN MENULIS HASIL OBSERVASI DALAM BENTUK PARAGRAF NARASI - Dian Puspita; Sariyah Astuti (LPPM STKIP PGRI Bandar Lampung, 2021)
The results of the research on class X students at SMA Muhammadiyah 1 Pringsewu on the ability to write observations in the form of paragraphs experienced difficulties in identifying topics, generating and developing a frame of mind, then spelling errors in Indonesian. The purpose of this study was to determine the ability of students in writing paragraphs containing observations of observations in the form of narrative paragraphs. The research method used is narrative. Analysis of the data used is a test using formulas related to assessment metrics. The results showed that for the 2020-2021 academic year, the percentage of class X students with an average ability score of 67 in the first semester of SMA Muhammadiyah 1 Pringsewu scored in the sufficient category, because students were not enthusiastic in reading books related to narrative texts, the teacher does not use media and methods that are less attractive to use in the learning process, and the available references are limited in the library.